Young adults have worse kidney transplant outcomes than other age groups. Issue 6 (27th May 2020) - Pankhurst, Tanya; Evison, Felicity; Mytton, Jemma; Williamson, Samantha; Kerecuk, Larissa; Lipkin, Graham
Abstract: Background: The objective of this study was to establish if renal transplant outcomes (graft and patient survival) for young adults in England were worse than for other age groups. Methods: Outcomes for all renal transplant recipients in England ( n = 26 874) were collected from Hospital Episode Statistics and the Office for National Statistics databases over 12 years. Graft and patient outcomes, follow-up and admissions were studied for all patients, stratified by age bands. Results: Young adults (14–23 years) had substantially greater likelihood [hazard ratio (HR) = 1.26, 95% confidence interval (CI) 1.10–1.19; P < 0.001] of kidney transplant failure than any other age band. They had a higher non-attendance rate for clinic appointments (1.6 versus 1.2/year; P < 0.001) and more emergency admissions post-transplantation (25% of young adults on average are admitted each year, compared with 15–20% of 34- to 43-year olds). Taking into account deprivation, ethnicity, transplant type and transplant centre, in the 14- to 23-year group, return to dialysis remained significantly worse than all other age bands (HR = 1.41, 95% CI 1.26–1.57). For the whole cohort, increasing deprivation related to poorer outcomes and black ethnicity was associated with poorer outcomes. However, neither ethnicity nor deprivation was over-represented in the young adult cohort. Conclusions: Young adults who receive a kidney transplant have a significant increased likelihood of a return to dialysis in the first 10 years post-transplant when compared with those aged 34–43 years in multivariable analysis.